Search for the direct production of charginos and neutralinos in final states with tau leptons in √s=13TeV pp collisions with the ATLAS detector - Onofre, A. (2018)
A search for the direct production of charginos and neutralinos in final states with at least two hadronically decaying tau leptons is presented. The analysis uses a dataset of pp collisions corresponding to an integrated luminosity of 36.1 fb, recorded with the ATLAS detector at the Large Hadron Collider at a centre-of-mass energy of 13 TeV. No significant deviation from the expected Standard Model background is observed. Limits are derived in scenarios of pair production and of and production in simplified models where the neutralinos and charginos decay solely via intermediate left-handed staus and tau sneutrinos, and the mass of the state is set to be halfway between the masses of the and the (chi) over tilde (0.)(1) . Chargino masses up to 630 GeV are excluded at 95% confidence level in the scenario of direct production of for a massless (chi) over tilde (0.)(1). Common and masses up to 760 GeV are excluded in the case of production of and assuming a massless . Exclusion limits for additional benchmark scenarios with large and small mass-splitting between the and the are also studied by varying the mass between the masses of the and the (chi) over tilde (0.)(1)